A Case Report of the Reconstruction of a Bone Defect Following Resection of a Comminuted Fracture of the Lateral Clavicle Using a Titanium Prosthesis - Abdalbary, Sahar Ahmed; Amr, Sherif M.; Abdelghany, Khaled; Nssef, Amr A.; El-Shaarawy, Ehab A. A. (Frontiers in Surgery, 2021)
.